COVID-19 vaccination status and associated factors among patients presenting with COVID-19-like symptoms in Uganda - Kusemererwa, Sylvia; Ankunda, Violet; Ongaria, Terry A.; Abaasa, Andrew; Kakande, Ayoub; Ssemwanga, Deogratius; Kimbugwe, Geofrey; Nayiga, Bernadette; Bosa, Henry K.; Driwale, Alfred; Yonas, T. Woldemariam; Kisakye, Annet; et al. (Vaccine, 2025)
The emergence of new SARS-CoV-2 variants threatens the effectiveness of global vaccination campaigns. This study examines the vaccination status and associated factors among patients presenting with COVID-19-like symptoms at 19 healthcare facilities in Uganda. Materials and methods A cross-sectional analysis was conducted using data collected at health facilities to evaluate the effectiveness of COVID-19 vaccines in Uganda from March 2023 to March 2024. Participants were individuals aged 12 years and older with COVID-19-like symptoms who underwent a SARS-CoV-2 qPCR test within 10 days of symptom onset. The study involved obtaining informed consent, collecting medical and vaccination histories (confirmed using vaccination cards and Ministry of Health COVID-19 database), performing physical examinations, administering a questionnaire, and taking oral/nasopharyngeal swabs for SARS-CoV-2 qPCR testing. Vaccination coverage was defined as receiving at least one vaccine dose. Logistic regression was used to identify factors associated with vaccination status. Results Among 1398 participants enrolled (55.4 % female), the median age was 30.0 years (IQR: 24.0–41.0). Vaccination coverage, was 66.6 %. Residing in Wakiso district compared to the Capital, Kampala was associated with a higher likelihood of vaccination (adjusted odds ratio [aOR] = 1.4, 95 % CI: 1.0–1.8, p = 0.021). Frontline and healthcare workers were more likely to be vaccinated (aOR = 5.0, 95 % CI: 3.6–7.3, p < 0.001), as were individuals with a previous COVID-19 diagnosis (aOR = 2.4, 95 % CI: 1.6–3.9, p < 0.001). Conclusions Our results underscore the need for targeted public health messaging and support to promote vaccination, especially among non-healthcare workers. Addressing these gaps is crucial for maintaining high vaccination coverage and mitigating the impact of new SARS-CoV-2 variants on the population.